ACTR-54. PATTERN OF RECURRENCE AND IMPACT ON SURVIVAL OF SALVAGE THERAPIES IN LOW-GRADE GLIOMAS FOLLOWING DOSE-DENSE TEMOZOLOMIDE. (5th November 2018) - Pellerino, Alessia; Rudà, Roberta; Pace, Andrea; Maria, Carmine Carapella; Dealis, Cristina; Caroli, Manuela; Faedi, Marina; Marchese, Giulia; Bello, Lorenzo; Soffietti, Riccardo
Abstract: INTRODUCTION: Initial chemotherapy with temozolomide (TMZ) may provide some benefit in high-risk low-grade gliomas. No standard treatment is validated at progression. The aim of the study was to investigate which is the optimal salvage therapy after the first progression in terms of PFS and the overall survival (OS). PATIENTS AND METHODS: We evaluated 49 patients with grade II oligodendroglioma and oligoastrocytoma according to WHO 2007 included in a phase II AINO trial, who progressed following initial chemotherapy alone with TMZ. Molecular data were available in 48 patients: 29 patients were IDH 1/2 mutated, 23 1p/19q codeleted, and 36 MGMT methylated. Median follow up was 140 months. RESULTS: All patients had local tumor progression and patterns on MRI were as follows: a FLAIR lesion in 25 patients (51.0%), a mild patchy enhancing lesion in 14 (28.6%), and a nodular enhancing lesion in the other 10 (20.4%). Twenty-four patients (49%) underwent a second-line chemotherapy, 12 (24.5%) a salvage radiotherapy, 11 (22.4%) a second surgery (10 gross-total resection and 1 subtotal resection), and 2 (4.1%) palliative care. Responses (RANO criteria) following salvage radiotherapy or chemotherapy consisted in PR in 6/38 patients (15.8%), MR in 9/38 (23.7%), SD in 10/38 (26.3%), and PD in 13/38 (34.2%). Median PFS after first salvage therapy was 18 months (IC95% 11–27). Median PFS was 11 months (IC95% 8–74) after radiotherapy, 14 months after chemotherapy and 31 months after surgery (IC95% 18–51, p 0.013). Median OS from the first salvage therapy was 63 months (IC95% 4 - NR). Median OS was 44 months (IC95% 4 NR) after radiotherapy, 38 months (IC95% 22–80) after chemotherapy, and 87 months after surgery (IC95% 11-NR, p 0.09). CONCLUSIONS: Reoperation aiming at total or near/total resection seems to offer a probability of a longer PFS and OS compared with the other treatment options.